Koziiat rog - Andonov, Metodi (Bulgaria : Studio for Feature Films, 1971)
The film takes us back to the 18th century when Bulgaria was a part of the Ottoman Empire. Four hoodlums break into the house of the shepherd Karaivan, raping and killing his wife. The young shepherd’s daughter, Maria, witnesses the rape and death of her mother. Karaivan decides to take the law into his own hands and becomes obsessed by his violent wish for revenge. He cuts Maria’s hair, dresses her in man's clothes and raises her as a boy so that she can kill in cold blood. The goat horn becomes a symbol of revenge. After 9 years she has found the four violators and managed to kill three of the men with the goat horn, but before killing the last one, in the rich oriental house Maria is unwitting witness to a love scene and a change comes over her. From time to time she secretly dons a beautiful dress and exults in her newly found female identity. She falls in love with a young shepherd and the hatred melts in her heart. When Karaivan discovers the change in her it is already too late. He tries to bring her back to revenge by killing the young lover. The father sets his hut on fire, but without suspecting it, kills the daughter who is also there.
Duration: 01:43:00
Keywords: Fiction films